2022
DOI: 10.3390/antiox11091638
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effects of Dietary Supplements on Adult COVID-19 Patients: Why Do We Not Also Use Them in Children?

Abstract: Respiratory tract infections (RTIs) are very common in children, especially in the first five years of life, and several viruses, such as the influenza virus, Respiratory Syncytial Virus, and Rhinovirus, are triggers for symptoms that usually affect the upper airways. It has been known that during respiratory viral infections, a condition of oxidative stress (OS) occurs, and many studies have suggested the potential use of antioxidants as complementary components in prophylaxis and/or therapy of respiratory vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 96 publications
0
13
0
Order By: Relevance
“…In this regard, it has been demonstrated that disulfiram, a thiol‐reacting Food and Drug Administration (FDA)‐approved drug, is able to inhibit MERS‐CoV and SARS‐CoV proteases [74]. In addition, a recent review has highlighted the valuable role of anti‐oxidants (flavonoids, lactoferrin, melatonin, zinc, selenium, resveratrol) in preventing and treating SARS‐CoV‐2 infection [75]. Based on currently available data, we envision that carbocysteine may affect these main targets: inhibition of SARS‐CoV‐2 binding, protease/anti‐protease imbalance, ROS scavenging, and inhibition of various redox signalling pathways (Figure 3).…”
Section: Mechanisms Of Action Of Carbocysteinementioning
confidence: 99%
“…In this regard, it has been demonstrated that disulfiram, a thiol‐reacting Food and Drug Administration (FDA)‐approved drug, is able to inhibit MERS‐CoV and SARS‐CoV proteases [74]. In addition, a recent review has highlighted the valuable role of anti‐oxidants (flavonoids, lactoferrin, melatonin, zinc, selenium, resveratrol) in preventing and treating SARS‐CoV‐2 infection [75]. Based on currently available data, we envision that carbocysteine may affect these main targets: inhibition of SARS‐CoV‐2 binding, protease/anti‐protease imbalance, ROS scavenging, and inhibition of various redox signalling pathways (Figure 3).…”
Section: Mechanisms Of Action Of Carbocysteinementioning
confidence: 99%
“…Of the 93 narrative reviews included in the live review, 16 were originally identified for the nutraceuticals section and 15 were included (see Table 1). [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Of those, 6 were from the region of the Americas (Brazil, 19,20 Argentina, 21 Canada, 22 Mexico, 23 USA 24 ), 5 from the European region (Italy, 25,26 Denmark, 27 Romania, 28 Russia 29 ), 2 from the South-East Asia region (India, 30 Korea 31 ), and one each from the Western Pacific region (Australia 32 ) and Eastern Mediterranean region (Iran 33 ). The individual nutraceuticals covered by these reviews included melatonin, 20,21,25,26,28,29,31,33 quercetin, 23,26,27,30,31 PUFAs, 22,24,27,32 probiotics, 19,24,…”
Section: Narrative Reviewsmentioning
confidence: 99%
“…The anti-oxidant (n = 3), anti-inflammatory (n = 6), and immune modulating (n = 4) properties were the main focus of the narrative reviews on melatonin. 20,21,26,28,29,30,33 Several of the reviews suggested that the actions of melatonin may be valuable for reducing complications from COVID-19 via suppression of the cytokine storm as well as improving long-term outcomes via neuroprotective effects, 26,29,31 and sleep regulation. 20,21,29 The benefits of melatonin in high-risk, aging populations and in those with long CV was also covered.…”
Section: Melatoninmentioning
confidence: 99%
“…21 Of the 12 narrative reviews initially identified, eight (67%) remained for the final umbrella review after exclusion criteria were applied (Table 2). Based on the country of residence of the first author, two of the reviews were conducted from the USA, 22,23 while the others include one each from Australia, 24 Iran, 25 Italy, 26 Romania, 27 Serbia, 28 and Poland. 29 The minerals reviewed were copper, 25,27,28 iron, 28 magnesium, 25 selenium 23,[25][26][27][28][29] and zinc.…”
Section: Narrative Reviewsmentioning
confidence: 99%
“…Based on the country of residence of the first author, two of the reviews were conducted from the USA, 22,23 while the others include one each from Australia, 24 Iran, 25 Italy, 26 Romania, 27 Serbia, 28 and Poland. 29 The minerals reviewed were copper, 25,27,28 iron, 28 magnesium, 25 selenium 23,[25][26][27][28][29] and zinc. [22][23][24][25][26][27][28] Five of the narrative reviews focused on both prevention and treatment, 22,[24][25][26][27] two on prevention, 23,29 and one on treatment.…”
Section: Narrative Reviewsmentioning
confidence: 99%